Pengaruh Pajak Tangguhan dan Penghindaran Pajak terhadap Manajemen Laba pada Perusahaan Manufaktur Subsektor Industri Dasar dan Kimia Tahun 2019-2023 - Wilson, Wilson; Latersia Br. Gurusinga; Juliandi Sahputra (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
This study aims to determine the effect of deferred tax and tax avoidance on earnings management. The object of this research is companies in the Basic and Chemical Industry sub-sector listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period, with an observation period of five years. A total of 26 companies were selected as samples using purposive sampling technique. Data analysis was conducted using classical assumption tests and hypothesis testing. The results show that partially, deferred tax has no effect and is not significant on earnings management, and tax avoidance has a negative but not significant effect on earnings management. Simultaneously, the variables of deferred tax and tax avoidance have no effect and are not significant on earnings management. The coefficient of determination value obtained is 0.016, which means that earnings management is influenced by deferred tax and tax avoidance variables by 0.16%, while the remaining 99.84% is influenced by other factors outside this research model, such as profitability, solvency, and others.